Konsumsi Jus Bayam Merah Campur Madu terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Trimester III - Neneng Siti Lathifah; Susilawati Susilawati (Jurnal Kesehatan, 2019)
In pregnancy, there is erythroid hyperplasia of the bone marrow and increases the period of Red Blood Cell (RBC). However, a disproportionate increase in plasma volume results in hemodilution. Anemia occurs in 1/3 of women during the third trimester, and the most common cause is iron deficiency. The results of a preliminary study at BPM Wirahayu in August 2018, found 125 pregnant women with 25% of mothers having mild anemia, 10% moderate anemia and 0.7% severe anemia. The purpose of this study is that red spinach juice mixed with honey can increase hemoglobin levels. Research Design with Pre Experiment Method with Two Group Pretest Posttest design. The population is all pregnant women with anemia in BPM Wirahayu Bandar Lampung as many as 57 people from April to July 2019. The sampling technique uses purposive sampling. A sample of 40 people according to inclusion and exclusion,criteria. The results of the average analysis of hemoglobin in pregnant women before given red spinach juice mixed with honey is 9,795g/dl with a minimum Hb of 8,3g/dl and a maximum of 10,5g/dl and the average hemoglobin in pregnant women after honey red spinach juice mixed with honey is 11,495g/dl with a minimum Hb of 10,7g/dl and a maximum of 13,0g/ dl. The results of the analysis of the average hemoglobin before the control is 10,305g/dl with a minimum Hb of 10.0 g/ dl and a maximum Hb of 10,5g/dl, the average hemoglobin after the control is 10,795g/dl with a minimum Hb 10,6g/dl and maximum Hb 11,1g/dl. Bivariate analysis showed p-value of 0,000<0,05. There is a significant influence between the consumption of Red Spinach Juice mixed with honey on hemoglobin levels in pregnant women at BPM Wirahayu Bandar Lampung in 2019.